2024
DOI: 10.1007/s10682-024-10297-1
|View full text |Cite
|
Sign up to set email alerts
|

Under pressure: evidence for selection on color-related genes in poison frogs of the genus Ranitomeya

Andrew O. Rubio,
Adam M. M. Stuckert,
Troy M. LaPolice
et al.

Abstract: Aposematic organisms rely on their bright conspicuous coloration to communicate to potential predators that they are toxic and unpalatable. These aposematic phenotypes are strongly tied to survival and therefore make excellent opportunities to investigate the genetic underpinning of coloration. The genus Ranitomeya includes phenotypically diverse members of Neotropical aposematic poison frogs native to South America. Significant progress has been made in elucidating the molecular mechanisms responsible for apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…The xanthine hydrogenase (xdh), initially described as the rosy locus in Drosophila, is known to influence eye coloration 71 . It is also a gene involved in the pteridine synthesis pathway in amphibians 27 that has been shown to be under selection in dendrobatids 72 . It is also differentially expressed in different color morphs of D. auratus 70 .…”
Section: Patternmentioning
confidence: 99%
“…The xanthine hydrogenase (xdh), initially described as the rosy locus in Drosophila, is known to influence eye coloration 71 . It is also a gene involved in the pteridine synthesis pathway in amphibians 27 that has been shown to be under selection in dendrobatids 72 . It is also differentially expressed in different color morphs of D. auratus 70 .…”
Section: Patternmentioning
confidence: 99%
“… Liu et al 2014 ; Posso-Terranova and Andrés 2017 ; Stuckert et al 2019 ; Rodríguez et al 2020 ; Stuckert et al 2024 ; Twomey, et al 2020a ). In addition, several studies have identified genes related to color development under positive selection in aposematic species ( Rodríguez et al 2020 ; Linderoth et al 2023 ; Rubio et al 2024 ). Historically, evolutionary biologists have predicted that aposematism, driven by predator-imposed selective pressures, causes sympatric phenotypes among closely related species to converge on a single color pattern to promote accelerated predator learning ( Müller 1879 ; Mallet and Joron 1999 ).…”
Section: Introductionmentioning
confidence: 99%